PENERAPAN HUKUM KONTRAK PADA USAHA ASURANSI SYARIAH MENURUT FIKIH MUAMALAH (Studi di PT Asuransi Takaful Keluarga Cabang Malang) - choliq subekti (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTThis study aims to describe and analyze the problem of applying contract law and engagement law in sharia insurance business according to Muamalah fiqh. The focus of the study is the discussion of three things, namely the mechanism of making contracts (contracts) between sharia insurance companies and customers, the factors that cause the abolition of an agreement and its legal consequences, and how to resolve disputes if one party between the company and the customer does default. The chosen research location is PT Syarikat Takaful Indonesia Malang Branch. The results of this study indicate that there are several contracting mechanism (contract) between PT Syarikat Takaful Indonesia and prospective customers, the things that become a factor of the cancellation of the agreement, and if there is a dispute between the customer and the company, then two methods of settlement can be taken, namely non-litigation and litigation methods.Â Keywords: Law of Engagement, Sharia Insurance, Mu'amalah Fiqh